2012
DOI: 10.1002/lary.23622
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of oropharyngeal cancer patients with respect to treatment strategy and p16‐positivity

Abstract: Early disease can be treated with high long-term QoL by surgery alone. Primary surgery with postoperative RT in selected patients with limited primary tumors and advanced neck disease renders excellent QoL. Our results suggest that IMRT is superior to former radiation techniques with regard to QoL, and should be considered as standard of care in patients undergoing RT for OPSCC. Patients with p16 positive tumors appear to show not only a better outcome but also report on a better QoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 57 publications
6
49
1
1
Order By: Relevance
“…53 Minimizing and focusing XRT, while avoiding chemotherapy lead to less treatment toxicity and improved outcomes. 5355 Patients with early stage disease treated with surgery alone, demonstrate superior outcomes by avoiding the toxicity of XRT. 27,54,56 Although this data is still in its infancy, TORS is showing promise as an optimal treatment strategy in early stage disease.…”
Section: Commentmentioning
confidence: 99%
“…53 Minimizing and focusing XRT, while avoiding chemotherapy lead to less treatment toxicity and improved outcomes. 5355 Patients with early stage disease treated with surgery alone, demonstrate superior outcomes by avoiding the toxicity of XRT. 27,54,56 Although this data is still in its infancy, TORS is showing promise as an optimal treatment strategy in early stage disease.…”
Section: Commentmentioning
confidence: 99%
“…Management decisions must be based on the likelihood of cure as well as the resulting structural, cosmetic, and functional deficits, which can negatively impact quality of life (QoL) [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…13 Radiation therapy as a negative factor in quality of life measures has been found in other studies as well. Broglie et al 66 found that both IMRT and surgery provide better measures than conventional radiation, and Leonhardt et al 67 reported that patients receiving TORSonly procedures had improved functional status compared with patients receiving TORS combined with adjuvant therapy. Transoral robotic surgery may therefore be used to enhance quality of life by decreasing long-term functional sequelae associated with radiation.…”
mentioning
confidence: 99%